(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This research is devoted to study the soldering of Sn-Pb alloy on different part (copper, low carbon steel, brass) .the Sn-Pb alloy produced in different percentage of Pb and addition of Ag by casting, and show the effect on electrochemical, mechanical and electrical properties. The mechanical and physical properties includes microstructure, tensile, electrical conductivity and electrochemical have been achieved for this research through tests that include microstructure test, tensile test, tafel Potentiostatic, electrical conductivity test, X-Ray Fluorescent Analysis (XRF). From results obtained in this study, a higher tensile strength was found for (Sn97%+Pb1.5%+Ag1.5%) when its compared with other alloy, and the best result in soldering was with carbon steel because it has higher strength compared with brass andcopper. The electrical conductivity result showed that the alloy (Sn97%+Pb1.5%+Ag1.5%) has higher electrical conductivity.